Endoscopic Removal of Displaced Sagittal Intracapsular Condylar Fracture - Trento, Guilherme Dos Santos; Gorla, Luis Fernando de Oliveira; Rodrigues, Marcos Marques; Pereira-Filho, Valfrido Antônio (Wolters Kluwer, 2017)
Fractures involving the mandibular condyle are among the most common fractures of facial bones and still generate great discussion concerning therapeutic issues. Several factors have influence on the decision of treatment management of these fractures. In some patients, even when there is displacement of fractured fragments, the choice for conservative treatment is made. However, the removal of the condyle fragment may be required. In the oral surgery scope, endoscopy is a procedure used in many areas, and can be helpful to improve the visualization of surgical sites with difficult access. The endoscopic surgery brings benefits to patient such as no scar or minimal scar, lower risk to nerve damage, and decreased of surgical trauma and bleeding. In addition, according to surgeon experience, the surgery may become more dynamic. The aim of this study is to present an endoscopic technique associated with a transoral approach to remove a displaced sagittal intracapsular condyle fragment. Furthermore, to expose the advantages and benefits of this technique as well as the satisfactory results achieved.